Educação digital - Okida, Estela Silva [UNESP]; Perticarrari, Amanda Liz Pacifico Manfrim [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This article approaches the digital education of public schools importance in the city of Jaboticabal/SP, in order to prepare the students in the use of resources that computer can offer, by means off estimulating social and professional development, benefiting the future entry into the labor market.

Esse artigo aborda a importância da educação digital nas escolas públicas do município de Jaboticabal/SP, afim de preparar os alunos na utilização dos recursos que o computador pode oferecer, de modo a estimular o desenvolvimento social e profissional, beneficiando o futuro ingresso no mercado de trabalho.
Keywords: Digital education; Computer; Educação digital; Computador